CEFTA and the Process of Enlarging the European Union – The Case of Asymmetric Negotiations (Czech Journal of International Relations, 1999)
The negotiations of the CEFTA member states on admission to the European Union are analysed by the author in light of the theory of contractual (especially asymmetric) negotiations.The first (and biggest) section of the essay outlines the main features of the considerable structural superiority of the negotiating position of the European Union (economic strength as well as the attraction of a big market, a well-prepared and firm contractual institutional embedding of the association of members of the European Union) on the one hand, and on the other hand, the astutely applied tactical instruments, exploiting and further strengthening this advantage. These instruments include the principle of “the acquis and nothing but the acquis” (which is a type of tactic of tying one’s hands), and the impermissibility of demands of institutional or budgetary modifications and negotiations “in waves”.In evaluation and in the actual admission negotiations the European Union applies these tactics of strength which were reinforced strategically in this wave by “pre-admission partnership”. In this way, candidate countries were ostentatiously given the choice of whether (but above all how quickly) to accept the “acquis”, but whoever wished to be included in a speedy track (into the first wave) had no other choice than to agree. In the second section of the essay, tactics have been selected from the world literature on international negotiations with the help of which the candidate countries (especially the CEFTA member states) were able in theory to stand up in part to the method of threats – pile-drivers – applied by the European Union, thus reinforcing their relatively weaker negotiating position. These are tactics of cooperation between negotiating countries (somewhat related to the previously known negotiations of governments in accord).In the concluding part, there is the assertion that the normal system of tactics is accessible to the applicants of membership in the European Union only to a very limited degree if they do not cooperate. The joint procedure of the CEFTA countries is, however, most unlikely, because of the very small tradition of cooperation (see the activity of the Visegrad group) as well as because of the excessive differences between the countries included in the first group and their inadequate mutual confidence.